2022
DOI: 10.1007/s10865-022-00317-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine uptake and attitudes towards mandates in a nationally representative U.S. sample

Abstract: varying mandate support based on demographics, COVID-19 vaccine attitudes, and the scope of the mandate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
4
17
0
Order By: Relevance
“…The acceptance of mandates was high, with 70% strongly or somewhat approving vaccine mandates for use of public transport or employment and employment benefits. This contrasts with some data from western nations that suggest lower mandate acceptance rates, that are often driven by factors such as age, gender, political affiliations, perceptions of vaccine safety and effectiveness, and trust in regulatory processes [25][26][27]. Recent data from Columbia, El Salvador, and Spain show high rates of support of mandates, but low support for active measures such as suspension from work for those refusing vaccination [28].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The acceptance of mandates was high, with 70% strongly or somewhat approving vaccine mandates for use of public transport or employment and employment benefits. This contrasts with some data from western nations that suggest lower mandate acceptance rates, that are often driven by factors such as age, gender, political affiliations, perceptions of vaccine safety and effectiveness, and trust in regulatory processes [25][26][27]. Recent data from Columbia, El Salvador, and Spain show high rates of support of mandates, but low support for active measures such as suspension from work for those refusing vaccination [28].…”
Section: Discussionmentioning
confidence: 65%
“…Vaccine mandates historically have been an important tool in improving vaccine uptake rates [ 24 ]. Attitudes to mandates are well described in western cohorts with limited data in African populations [ 25 ]. We evaluated attitudes towards vaccine mandates in an African cohort composed of individuals who decided to accept vaccination one year after initiation of the national vaccine program.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study build upon and extend the existing scholarship, as well as provide implications for public health officials and political leaders. This study is amongst the first to look at support for mandates for specific occupations and demographic groups ( Attwell et al., 2021 ; Harris et al., 2022 ). Support for vaccine mandates across occupations has been understudied, particularly mandates for nursing home and police personnel.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to narrower mandates, a study conducted in the United States found that political partisanship drove support for both student and teacher mandates across different educational settings ( Haeder, 2021 ). People who lean toward political liberalism are more likely to support COVID-19 vaccine mandates for health care workers as well as for air and train travelers ( Harris et al, 2022 ). The politicization of the pandemic is not confined to the US; a study conducted in Australia found that support for mandatory COVID-19 vaccination was based on political party identification ( Smith et al, 2021 ).…”
Section: Attitudes Towards Covid-19 Vaccine Mandates For Various Groupsmentioning
confidence: 99%
“…For example, examining human papillomavirus vaccine uptake in young adult women found that attitudes, as predicted by the theory of planned behavior, were related to vaccination behavior through intentions [ 16 ]. Studies conducted in the context of COVID-19 vaccination [ 17 , 18 ], childhood vaccination [ 19 ], H1N1 (swine flu) vaccine [ 20 ], MMR vaccine [ 21 ], etc. have confirmed the link between attitudes and vaccination intentions/behavior.…”
Section: Introductionmentioning
confidence: 99%